Maltrato psicológico en una relación matrimonial, influenciado por la pandemia covid- 19, en la Parroquia La Unión - Tunay Veliz, Julecsy Marilin (2021)
In this case study, the topic Psychological abuse in a marital relationship, influenced by the Covid-19 pandemic, in La Unión Parish was addressed, with the aim of collecting the necessary data to know how the pandemic influences psychological abuse in marital relationships, this information was collected through interviews and psychometric instruments such as the FF-SIL Intrafamily Relationship Assessment Test and the Test of the person in the rain. The psychological tests gave us as a result that the patient is in a dysfunctional family and has problems of anxiety, insecurity, fear caused by the mistreatment received by her partner. Arriving at the diagnosis according to the ICD-10: Y07.- Other abuse syndromes include: mental abuse, physical abuse, sexual abuse, torture. It should be noted that the couple conflict affects the victim in a negative way, for which a therapeutic scheme based on the cognitive-behavioral approach was developed in order to modify, eliminate or reduce negative emotions and behaviors.